PENGARUH HEDONIC SHOPPING MOTIVATION DAN SALES PROMOTION TERHADAP IMPULSE BUYING PADA KONSUMEN TOKO FASHION ONLINE ZALORA - Endah Sari Titi Utami; Syarifah Hudayah; Asnawati Asnawati (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
This study aims to determine the effect of Hedonic Shopping Motivation and Sales Promotion on Impulse Buying in Zalora Online Fasion Store. The sampling technique used is to take the entire population to be used as research sampel, so the sample used in this research is as much as 108 respondents. Data analysis method used is multiple linear regression analysis. The results of the test show that the Hedonic Shopping Motivation and Sales Promotion have a significant positive effect on Impulse Buying in Zalora Online Fashion Store.Keywords : Hedonic Shopping Motivation, Sales Promotion, Impulse Buying